ASUHAN KEPERAWATAN NYERI KRONIS PADA TN.S DENGAN RHEUMATOID ARTHRITIS DI PUSKEMAS KALIBAGOR - Ismi Nur Aprilia; Madyo Maryoto; Arni Nur Rahmawati (Bajang Institute, 2022)
Rheumatoid Arthritis (RA) is a chronic inflammatory disorder of auto-immune or autoimmune response, a person's immune system can be disturbed and decreased which causes the destruction of the joint organs and synovial lining, especially in the hands, feet and knees. The role of nurses as care providers to provide services holistically in carrying out independent actions of nurses. This scientific paper uses a descriptive case study design that describes the Nursing Care of Chronic Pain in Tn.S with Rheumatoid Arthritis at the Kalibagor Health Center. The result is that Mr. S is still in a healthy and independent state despite his joint pain. However, with age, it is not impossible that later Tn S will experience an increase in the decline in physiological functions due to the aging process so that various other diseases can also appear. This is a normal condition in the aging process.